An epidemiology of self-reported cancer in India: A Decomposition analysis based on women in late-reproductive age-group - S.K. Singh; Ayantika Biswas; Parul Puri (Elsevier, 2021)
Background/Objectives: Cancer is a leading cause of adult deaths globally. Among women, breast cancer is a predominant cause of cancer mortality, accounting for almost a quarter (23%) of all cancer deaths worldwide. India has huge underlying regional and sectoral (urban-rural) variations, which extend even up to lifestyles and variations in age-specific death rates. This study aims to assess the social and regional variations and the contributions of selected cancer indicators in the country among women in the late reproductive age-group. Methods: National Family Health Survey (2015-16) data (Demographic Health Survey of India) has been used for this study. Results: The age-adjusted prevalence of cancer among women in India is 250 per 100,000 women. The results of the concentration indices show an overall concentration of cancer towards the richer quintiles. Decomposition of the concentration index shows significant contribution from factors like a higher age, years of schooling between 5 and 9 years, rural places of residence, bearing of 1 or more children, and contraceptive use like IUD, hysterectomy or sterilization. Conclusion: A comprehensive strategy to combat chronic diseases like cancer includes actions minimizing exposure to risk factors at the population level, as well as reducing the risk for individuals at the higher risk level and can aid in furnishing early, medium-term and long-term effects.